POSTMODERNISM IN ANGELA CARTER’S NOVELS: THE BLOODY CHAMBER (1979) AND NIGHTS AT THE CIRCUS (1984) - Ibrahim, Juan Abdullah (International Journal of Psychosocial Rehabilitation, 2020)
Angela Carter’s are invitations to understand the meanings of postmodernism and Post- feminism. The latter presents portrayals of interpretations of different ways of oppressing women, and realizing the specific style of expressing such topics. Carter uses the fairy tale genre and violence to present her critical points against patriarchy. She concentrates on self-awareness of women as new samples novels of their self-consciousness state against the traditional portrayal of women’s submissive role through these gothic elements. This paper argues how The Bloody Chamber and Nights at the Circus are feminist texts due to the narrative procedure and certain strategies followed by Carter to clarify characterization and women’s subjectivity through their body against the male gaze. The aim is to show women’s struggle for achieving their female identity and their knowledge and curiosity urge them to be seen in a developing way. Magic realism is also another technique she uses when Fevvers’ body is shown while she presents her performances as an aerialist for people in the circus. BC is an abbreviate form of The Bloody Chamber and NC is an abbreviated form of Nights at the Circus.